S3 T Cell Responses to Vitamin D Are Blunted in Latent Tuberculosis. (19th November 2012) - Hawthorne, G; Zhang, J; Jeffery, L; Thickett, D; Turner, A
Abstract : Introduction: Low vitamin D status is associated with an increased risk of Mycobacterium Tuberculosis. Consistent with this, the active form of vitamin D, 1, 25(OH)2 D3 exerts potent effects on immune cells. T cells are thought to contribute to the control of latent tuberculosis in which patients are infected with Mycobacterium tuberculosis but show no signs or symptoms of the disease. How vitamin D influences T cell responses in latent patients is therefore of interest. It has been shown that the co-suppressive protein, CTLA4, which is expressed on regulatory T cells and induced in T cells upon activation, is strongly up regulated by vitamin D and that it increases the frequency of CTLA-4+FoxP3+ cells [1]. Furthermore, vitamin D conditioned T cells are functionally suppressive. In this study we have therefore compared the effect of vitamin D upon CTLA-4 expression and the frequency of CD25+ FoxP3+ CTLA4+ cells in healthy and latent TB patients. Methods: Peripheral blood cells from healthy control donors (n=21) and patients with latent tuberculosis (n=12) were cultured with SEB or PPD with or without 1, 25(OH)2D3 or inactive 25(OH)D3. CD25+ FoxP3+ CTLA4+ frequency and the median CTLA-4 expression (MFI) of CD25+ cells was then monitored after two days by flow cytometry. Results: 1, 25(OH)2 D3 significantly increased CTLA4 MFI in both healthy and latent populations following stimulation with SEB (p≤0.01) or PPD (P=0.026, 0008). 25(OH)D3 also enhanced CTLA-4 expression in SEB cultures (p≤0.01). Induction of CTLA-4 was however reduced in PPD cultures (median 121) compared to SEB (median 360). Interestingly, the magnitude of CTLA-4 induction by 1, 25(OH)2 D3 or 25(OH)D3 also differed for healthy and latent populations in response to SEB (1, 25(OH)2 D3 (p=0.01) and 25(OH)D3 (p=0.006), with a similar trend in PPD stimulated cells (p=0. 092). Conclusion: The shift towards a T reg population as a result of vitamin D is blunted in latent TB compared to health. Differential response of memory cells in latent disease could account for this. Jeffery, LE, et al., 1, 25-Dihydroxyvitamin D3 and IL-2 combine to inhibit T cell production of inflammatory cytokines and promote development of regulatory T cells expressing CTLA-4 and FoxP3. Journal of immunology, 2009. 183 (9): p. 5458–67.